The Analysis Of Marketing Mix Strategy Of Wood Processing In Increasing The Salling Margin - Bunyamin Bunyamin; Sultan Iskandar (Eduvest - Journal of Universal Studies, 2021)
The purpose of this study is to analyze whether the application of the marketing mix strategy through the SWOT formulation can increase the sales volume of processed wood. This research was conducted at the office of PT. Three "Rs" located at Jalan Sultan Abdullah No. 75 Makassar, with the research time required by the author is approximately 3 (three) months starting from the beginning of May to July 2009. The population in this study are all consumers who use processed wood products, for housing development purposes in South Sulawesi, especially in the city of Makassar in the last year, so the population in this study is unknown. While the sample is as many as 300 respondents. Sampling was used using a non-probability sampling approach and the judgment method. Based on the results of the application of SWOT analysis, it appears that the strategy used by PT. The three "Rs" of Makassar in increasing processed wood sales are implementing the SO strategy, which is to make strengths to take advantage of opportunities, then the WO strategy by minimizing weaknesses to maintain opportunities, then the ST strategy using strengths to overcome threats and WT strategies that minimize weaknesses and avoid threats.